Exchange Rate Pass-Through in Romania - Gueorguiev, Nikolay (IMF Working Papers; Working Paper ;, 2003)
Quantifying the size and speed of the exchange rate pass-through to prices is important for formulating monetary policy decisions in Romania. Using a recursive VAR model, this paper finds that (i) the pass-through is large and relatively fast, accounting for a sizable fraction of inflation; (ii) the pass-through from the exchange rate against the U.S. dollar is larger, if not faster, than the one from alternative exchange rate benchmarks; and (iii) the pass-through to producer prices seems to have moderated recently, while the same cannot be said yet for consumer prices.